Smart grid applications and developments - Hills, Peter; Li, Victor O.K; Balme, Richard; Mah, Daphne (Green Energy and Technology,, 2014)
'Smart Grid Applications and Developments' enriches understanding of today's energy and climate challenges.  It demonstrates how solutions require not only technological advances, but also political sensitivity; well-informed policy analysis, an improved understanding of stakeholders' perceptions, and innovative interdisciplinary collaboration. Providing a holistic and integrated understanding of technology-stakeholder-policy interactions in smart grid technologies, this book focusses on global and Pan-Asian perspectives while offering case studies that illustrate what we can learn from international experiences. The book is organised into five sections: Part 1 discusses the historical and conceptual aspects of smart grids. Part 2 introduces the technological aspects and showcases the current state of the art. Part 3 explores policy and governance dimensions through the conceptual lens of stakeholders' perspectives. Part 4 presents a collection of international case studies. Showcasing state-of-the-art R&D developments and new policy experiences, this book contributes to a better understanding of the governmental, institutional and political challenges concerning smart grids and helps formulate policy recommendations for successful smart grid deployment.